Impact of intensive treatment on serum methylglyoxal levels among individuals with screen-detected type 2 diabetes: the ADDITION-Denmark study - Jensen, Troels Mygind; Fleming, Thomas; Nawroth, Peter Paul (Acta diabetologica, 2015)
Methylglyoxal (MG) has been implicated in the development of micro- and macrovascular diabetic complications, but it remains unclear how current treatments of type 2 diabetes affect its circulating levels.